A novel approach for measuring treeline spatial complexity. (May 2019) - Spinsante, S.; Montalto, L.; Garbarino, M.; Malandra, F.; Weisberg, P. J.; Paone, N.; Scalise, L.
Abstract: Treelines, defined as ecotonal zones between closed forest and the uppermost trees, are particularly sensitive to global changes related to climate and anthropic activities. Different mechanisms of treeline formation can be detected as subtle differences in ecotonal structure, which in turn have important implications for how treelines function and potentially respond to global changes. So, it is of interest to be able to measure in a precise and quantitative way treelines' properties reflecting climate and land use changes. Classical tools adopted to measure treeline spatial patterns are not able to fully understand the limiting factors affecting them. This work presents a novel textural analysis of treeline spatial structure based on the measurement of surface roughness, and applies the corresponding metrics to twenty study areas at both Upper and Lower treelines, where all tree crowns have been mapped at high precision. Preliminary results are promising and motivate future and more extensive evaluations on bigger datasets.